2006
DOI: 10.1073/pnas.0605305103
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-driven spatial organization of highly confined polymers: Lessons for the bacterial chromosome

Abstract: Despite recent progress in visualization experiments, the mechanism underlying chromosome segregation in bacteria still remains elusive. Here we address a basic physical issue associated with bacterial chromosome segregation, namely the spatial organization of highly confined, self-avoiding polymers (of nontrivial topology) in a rod-shaped cell-like geometry. Through computer simulations, we present evidence that, under strong confinement conditions, topologically distinct domains of a polymer complex effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
442
9
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(495 citation statements)
references
References 45 publications
(34 reference statements)
19
442
9
1
Order By: Relevance
“…Blocking of replication in one replichore does not prevent segregation of loci on the other. It seems plausible that spontaneous chromosome segregation by entropic disentanglement of the chromosomal polymer (1,27,28) may provide the essence of the segregation mechanism. Therefore, the key to efficient and faithful segregation is likely to reside in chromosome organization itself and the processes that drive this organization, as well as independent replication by spatially separated replisomes tracking along the DNA and the subsequent decatenation by TopoIV.…”
Section: Vol 192 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking of replication in one replichore does not prevent segregation of loci on the other. It seems plausible that spontaneous chromosome segregation by entropic disentanglement of the chromosomal polymer (1,27,28) may provide the essence of the segregation mechanism. Therefore, the key to efficient and faithful segregation is likely to reside in chromosome organization itself and the processes that drive this organization, as well as independent replication by spatially separated replisomes tracking along the DNA and the subsequent decatenation by TopoIV.…”
Section: Vol 192 2010mentioning
confidence: 99%
“…Finally, thermodynamic considerations of the properties of a highly confined, self-avoiding polymer (representing a DNA molecule) in a rod-shaped cell-like geometry (representing a bacterial cell) have indicated that duplicated circular chromosomes could segregate spontaneously without any additional force in physiologically relevant timescales (1,27,28). Therefore, entropy alone may be sufficient to produce the observed segregation of replicated chromosomes, while plasmids use active partition systems because their small size in a "sea" of chromosomal DNA would not lead to effective spontaneous segregation.…”
mentioning
confidence: 99%
“…In vivo fluorescence microscopy showed that the speed of segregation of individual loci is too fast to be accounted for by attachment of sister chromosomes to a growing cell envelope (1,3,4), as had been proposed (5). These observations led to the suggestion that rapid segregation may be the consequence of nondedicated mechanisms, such as force exerted by the DNA or RNA polymerases (6,7) or entropic exclusion of sister chromosomes (8), all of which predict that the order of segregation will follow the order of replication. Alternatively, segregation may be driven by a dedicated mechanism acting on a centromeric sequence (9,10), in which case the first sequence to segregate would be the centromere regardless of when it is replicated.…”
mentioning
confidence: 96%
“…The ability to uncouple segregation from replication by moving parS away from Cori allowed us to determine whether nondedicated mechanisms are sufficient to effect chromosome segregation in Caulobacter, as has been suggested (8). The strain shown in Fig.…”
Section: Initiation Of Chromosome Segregation Requires Pars-directed mentioning
confidence: 99%
See 1 more Smart Citation